Accurate Assessment of Computed Order Tracking - P.N. Saavedra; C.G. Rodriguez (Shock and Vibration)
Spectral vibration analysis using the Fourier transform is the most common technique for evaluating the mechanical condition of machinery working in stationary regimen. However, machinery operating in transient modes, such as variable speed equipment, generates spectra with distinct frequency content at each time, and the standard approach is not directly applicable for diagnostic. The "order tracking" technique is a suitable tool for analyzing variable speed machines. We have studied the computed order tracking (COT), and a new computed procedure is proposed for solving the indeterminate results generated by the traditional method at constant speed. The effect on the accuracy of the assumptions inherent in the COT was assessed using data from various simulations. The use of these simulations allowed us to determine the effect on the overall true accuracy of the method of different user-defined factors: the signal and tachometric pulse sampling frequency, the method of amplitude interpolation, and the number of tachometric pulses per revolution. Tests on real data measured on the main transmissions of a mining shovel were carried out, and we concluded that the new method is appropriate for the condition monitoring of this type of machine.